PENGARUH PERUBAHAN KURIKULUM MADRASAH TERHADAP PENINGKATAN KARAKTER PESERTA DIDIK - Nurmiati; Firdaus; Muhammad Zulkarnain Mubhar (Lembaga Penelitian dan Pengabdian Masyarakat IAI Muhammadiyah Sinjai, 2022)
This research aims to knowing of changing the Madrasah curriculum on improving the character of students at MTS An Nur DDI Bengo, Bone Regency, knowing the influence of changes in the Madrasah curriculum on improving the character of students at MTS An Nur DDI Bengo, Bone Regency. This research is included in the type of ex post facto research using a quantitative research approach. The population in this study were the Head of Madrasah, Deputy Head of Curriculum and Akhlak Teachers and all students of MTS An Nur DDI Bengo, Bone Regency, while the sample consisted of 19 students and 3 education staff. The data collection techniques used in this study were questionnaires and documentation, while the data analysis used simple regression analysis techniques. The results of this study indicate that changes in the madrasa curriculum have an effect on improving the character of students at MTS An Nur DDI Bengo, Bone Regency. Based on the results of the simple regression test, the significance value of the effect of changing the madrasa curriculum on improving character is 0.012. The significance value obtained is smaller than (0.012 < 0.05). So it can be concluded that H0 is rejected and Ha is accepted, meaning that there is an effect of changing the Madrasah curriculum on improving the character of students at MTS An Nur DDI Bengo, Bone Regency. Similarly, the results of the T test using SPSS showed that Thit = 2,298 > Ttable = 2,201. so it can be concluded that H0 is rejected and Ha is accepted there is an effect of changing the Madrasah curriculum on improving the character of students at MTS An Nur DDI Bengo, Bone Regency. The magnitude of the influence given by the independent variable X (Changes in Madrasah curriculum) on the dependent variable Y (Improving the character of students) is 90.0%. While the rest (100% - 90.0% = 10.0%) is influenced by other variables.